HUBUNGAN ANTARA DUKUNGAN SOSIAL DENGAN HARGA DIIRI (SELF ESTEEM) SISWA KELAS VIII SMP NEGERI 8 PEKANBARU - Eka Lestari; H.Raja Arlizon; Hj. Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to 1) to know the description of student's social support 2) to understand the student's self-esteem 3) to establish the relationship between social support and student's self-esteem. The subjects of the study were the students of class VIII Determination of the sample using a total sample which means the whole population becomes the sample. The research method used is correlation method, this research is aimed to determine the relationship of a variable with other variables. The results showed that half of the sample had good social support 2) almost half of the sample already have high self esteem 3) there is a significant positive correlation between social support with student self esteem, where if social support obtained by student good then price Student self will increase.Keywords: Social Support, Self-esteem